2006
DOI: 10.1002/mame.200600284
|View full text |Cite
|
Sign up to set email alerts
|

Core‐Sheath Structure in Electrospun Nanofibers from Polymer Blends

Abstract: Summary: Electrospinning of polymer blends offers the potential to prepare functional nanofibers for use in a variety of applications. This work focused on control of the internal morphology of nanofibers prepared by electrospinning polymer blends to obtain core‐sheath structures. Polybutadiene/polystyrene, poly(methylmethacrylate)/polystyrene, polybutadiene/poly(methylmethacrylate), polybutadiene/polycarbonate, polyaniline/polycarbonate, and poly(methylmethacrylate)/polycarbonate blends were electrospun from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 22 publications
2
95
0
2
Order By: Relevance
“…S6b,c and Supplementary Note S2), a P3HT:PEO-blend NW has a coreshell structure along the wire axis. The origin of the core-shell structure of printed NW is explained by phase separation of polymer blends, which can be caused by the incompatibility or the large solubility parameter difference in solution 22 . On the basis of grazing-incidence X-ray diffraction (GIXRD) and polarized photoluminescence analysis for the aligned OSNWs, we found that the aligned NWs had long-range ordered nano-domains along the wire axis (Supplementary Figs S7 and S8, and Supplementary Notes S3 and S4).…”
Section: Resultsmentioning
confidence: 99%
“…S6b,c and Supplementary Note S2), a P3HT:PEO-blend NW has a coreshell structure along the wire axis. The origin of the core-shell structure of printed NW is explained by phase separation of polymer blends, which can be caused by the incompatibility or the large solubility parameter difference in solution 22 . On the basis of grazing-incidence X-ray diffraction (GIXRD) and polarized photoluminescence analysis for the aligned OSNWs, we found that the aligned NWs had long-range ordered nano-domains along the wire axis (Supplementary Figs S7 and S8, and Supplementary Notes S3 and S4).…”
Section: Resultsmentioning
confidence: 99%
“…Lu has a lower molecular weight than PCL and higher molecular mobility and consequently it migrates to the regions of highest shear rate (at the walls of the needle). The higher viscosity component (PCL) occupies mostly the center of the fiber [40].…”
Section: Swelling and Mass Lossmentioning
confidence: 99%
“…Multicomponent fibers can be obtained mainly by two techniques [5]: direct electrospinning of polymers solution (in a single-needle configuration, if a mixture of polymers is co-dissolved in the electrospinning solution or a multi-needle configuration in which the polymer solutions are separated in parallel or concentric syringes) and post-treatment of the single-component electrospun fibers (which can include coating with other inorganic-polymer layers [6,7], grafting [8], crosslinking [9], chemical vapour deposition [10], functionalization with other (bio)polymers [11]). In addition to the new physico-chemical properties that arise from using various components, a variety of fiber structures can be obtained such as core-shell fibers, micro/nanotubes, interpenetrating phase morphologies (matrix dispersed or co-continuous fibers) [12,13], nanoscale morphologies (spheres, rods, micelles, lamellae, vesicle tubules, and cylinders) [14] and multilayered constructs (either with different composition or different fiber diameter) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…A similar result was also observed by Yang et al 16 . In general, the ability to form coaxial electrospun fibres with fine core-shell interface depends on both process parameters and solution properties 17,32 . In this work, the effects of solution properties (i.e., electrical conductivity of the core and shell solutions) Fig.…”
Section: Properties Of Polymer Solutionsmentioning
confidence: 99%
“…Coaxial electrospinning thus exhibits more steady release rate behaviour 8,[14][15][16] . In addition, the shell matrix of the fibre can be tailored to provide additional functional properties 17,18 . Nevertheless, encapsulation of orally administered bioactive compounds using coaxial electrospinning has rarely been attempted.…”
Section: Introductionmentioning
confidence: 99%